Age as a risk factor for suicide - Kocić Sanja S.; Milić Časlav T.; Grbić Gordana G.; Plašić Aleksandar H.; Tatić Zoran V. (Vojnosanitetski Pregled)
Background/Aim. World Health Organization (WHO) in its plan for health policy until the year 2010, has taken reduction of risk factors of suicide as its 12th aim. Because of the fact that the problem of suicide is also significant health problem in our society, the aim of this study was to examine the influence of life period as a risk factor for suicide in the area of the town of Kragujevac. Methods. In total 211 persons, both sexes, aged between 17 and 91 years, from the area of the town of Kragujevac, who had been committed a suicide during the period from 1996 to 2005, were included in a retrospective study. This study included the analysis of: conditions prior to suicide, locations of suicide, motives for suicide, the ways of committing suicide. For statistical analysis χ2 test and univariante regression model were used. Results. Average rate of suicide, in analyzed period, moved from 8.7 to 27 with a mean value of 14.6± 6.9. Suicide rates were the lowest in the age group from 15 to 24 years and the highest in the age group above 65 years (p < 0.05). Among the presuicidal conditions, within any age groups the presence of mental disease dominated as a factor for suicide, but within the oldest one in which organic diseases prevailed as a factor for suicide (p < 0.05). Statistically significant fact is that a house (flat) was the main location for committing suicide in any age groups. Motives for suicide were significantly different within the groups and they were mostly unknown. Committing suicide by hanging was the most frequent way of suicide among any age groups. Univariant regression analysis failed to show any impact of age on the analyzed factors. Conclusion. Because of the fact that an average rate of suicide in elderly increases it is obligatory to primarily determine risk factors for suicide among people more than 65 years of age. Physicians should play the most important role in that.